1997
DOI: 10.1007/s004200050237
|View full text |Cite
|
Sign up to set email alerts
|

Blue-yellow deficiency in workers exposed to low concentrations of organic solvents

Abstract: This study gives further evidence that even mixtures of organic solvents at concentrations below the threshold-limit values may impair color vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 28 publications
3
20
0
1
Order By: Relevance
“…Since subjects with such diseases were excluded from the present study, medical reasons might not be significant for the observed changes in colour preferences with ageing. Likewise, occupational reasons, e.g., the exposure to organic solvents that might account for acquired colour vision defects [29], are not important for the present results, as the respective subjects were excluded from this study. Therefore, the main explanations for the present results may rely upon psychological and biological changes during the course of ageing.…”
Section: Age Differences In Colour Preferencesmentioning
confidence: 94%
“…Since subjects with such diseases were excluded from the present study, medical reasons might not be significant for the observed changes in colour preferences with ageing. Likewise, occupational reasons, e.g., the exposure to organic solvents that might account for acquired colour vision defects [29], are not important for the present results, as the respective subjects were excluded from this study. Therefore, the main explanations for the present results may rely upon psychological and biological changes during the course of ageing.…”
Section: Age Differences In Colour Preferencesmentioning
confidence: 94%
“…Emerging evidence suggests that occupational exposure to organic solvents may be associated with impairment of visual function in many respects, and in particular color vision, including losses of blue yellow color, and secondary red green color dyschromatopsia [185][186][187].…”
Section: Ocular Effectsmentioning
confidence: 99%
“…Muttray et al 4) examined 24 workers exposed to mixtures of solvents and 24 controls. They found a significantly lower CCI (median: 1.0) in exposed than in controls (1.17).…”
Section: Color Vision Dysfunction In Solvent-exposed Paintersmentioning
confidence: 99%
“…They are not relevant from a clinical point of view. Muttray et al 4) showed that CCI values of this magnitude do not restrict the suitability of workers, even in occupations such as printing, in which good color vision is usually necessary. Solvent induced color vision dysfunction is to a great extent or even completely reversible after exposure stops as was shown in the case of tetrachlorethylene and styrene 3,15) .…”
Section: Color Vision Dysfunction In Solvent-exposed Paintersmentioning
confidence: 99%
See 1 more Smart Citation